Effect of Carbon Nanotubes (CNTs) on the performance of Solid Rocket Propellants (SRPs): A short review - Weiqiang Pang; Xu Xia; Yu Zhao; Luigi T. DeLuca; Djalal Trache; Dihua OuYang; Saiqin Meng; Xiaogang Liu; Hongjian Yu (FirePhysChem, 2023)
Burning rate catalysts (BRCs) are usually utilized to adjust the burning rates of solid rocket propellants (SRPs). Carbon nanotubes (CNTs), for their unique structure and properties, have been studied by several researchers worldwide with a wide range of applications. In this paper, several worthy CNTs-based materials and effects are described. Specifically, the influence of CNTs on the thermal behavior of energetic materials (EMs) are discussed, and we investigated the impact of CNTs/metal (metal oxide, MO) composites on the thermal degradation of EMs. Applications for SRPs and solid rocket nozzle motors might benefit from a focus on the examination of the burning rate, pressure exponent characteristics, and hazardous aspects. It was discovered that CNTs, as opposed to the comparable micro-sized additives, can modify the combustion behavior and speed up the burning of SRPs. Lastly, the difficulties encountered in implementing some of these applications are also examined in terms of manufacturing, processing, pricing, and potential future uses.